Metabolic syndrome in antiphospholipid syndrome versus rheumatoid arthritis and diabetes mellitus: Association with arterial thrombosis, cardiovascular risk biomarkers, physical activity, and coronary atherosclerotic plaques - Bolla, Eleana; Tentolouris, Nikolaos; Sfikakis, Petros P.; Tektonidou, Maria G. (Frontiers in Immunology, 2023)
Background: Cardiovascular disease (CVD) is the foremost cause of morbidity and deaths in antiphospholipid syndrome (APS), driven by thrombo-inflammation and atherothrombosis mechanisms. Metabolic syndrome (MetS) is a proinflammatory and prothrombotic state characterized by increased CVD risk. We aimed to evaluate the prevalence of MetS in APS patients compared to rheumatoid arthritis (RA) and diabetes mellitus (DM) and its associations with clinical and laboratory patient characteristics and vascular ultrasound (US) markers of subclinical atherosclerosis. Methods: We included 414 patients in our study: 138 patients with APS (median age: 44.9 years, females 70%) and matched 1:1 for age and sex RA and DM subjects. Three sets of criteria were used for MetS diagnosis: Joint Interim Statement (JIS), International Diabetes Federation (IDF) and modified National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATPIII). The demographic, clinical and laboratory characteristics of all participants were recorded and carotid and femoral US was performed in patients with APS. Multivariate regression models were applied. Results: Prevalence of MetS was 23.9%, 23.2%, 20.3% (based on JIS, IDF, modified NCEP-ATPIII criteria, respectively) in APS versus 17.4%, 17.4%, 13% in RA (p=0.181, p=0.231, p=0.106, respectively), and 44.2%, 44.2%, 40.6% in DM patients. In multivariate analysis, patients with systemic lupus erythematosus- related APS had an approximately 2.5-fold higher risk of MetS versus RA patients. MetS in APS was independently associated with arterial thrombosis (Odds ratio 3.5, p=0.030). Odds ratio for MetS was 1.16 for each one unit increase in C-reactive protein levels according to JIS and IDF criteria, and 1.49 and 1.47 for each one unit increase in uric acid levels using the IDF and modified NCEP-ATPIII models, respectively. APS patients with atherosclerotic carotid plaques had 4 to 6.5-fold increased risk of MetS. Odds for MetS were decreased by 26% with an increase in physical activity by one hour per week. Conclusions: MetS is present in approximately one-fourth of APS patients at a comparable prevalence to that observed in patients with RA. MetS in APS is associated with arterial thrombosis, cardiovascular risk biomarkers, physical activity, and subclinical atherosclerosis, supporting its role in cardiovascular risk stratification and management in APS.